Pengaruh Kinerja Lingkungan, Pengungkapan Informasi Lingkungan, dan Good Corporate Governance pada Harga Saham Perusahaan - Gita Indah Dewi Fortuna, Ni Made; Putra, I Nyoman Wijana Asmara (E-Jurnal Akuntansi; Vol 30 No 4 (2020)DO - 10.24843/EJA.2020.v30.i04.p18, 2020)
This study aims to empirically examine the influence of environmental performance, environmental disclosure, and good corporate governance on stock prices of mining company listed in Indonesian Stock Exchange around 2014 to 2018. The research sample was selected using the non-probability sampling method with a purposive sampling technique and obtained as many as seven companies, so that the number of observations with a study period of 5 years was 35 observations. The data analysis was analysed by using the multiple linear regression technique. The result show that environmental performance, environmental disclosure, and good corporate governance positively affected companies’ stock prices in the market. Keywords: Stock Price; Environmental Performance; Environmental Disclosure; Good Corporate Governance.